MEANING AND ENTRIES DEFINING OF -ER- WORDS INFIXES IN INDONESIAN - Prima Hariyanto (Widyariset, 2015)
Some linguists have discussed Indonesian infix, includes forms and meanings. However, very few studies discuss infix in more detail, includes the development of its meaning. This article discusses -er- infixed words in Kamus Besar Bahasa Indonesia. This research uses descriptive method and the technique for collecting data is bibliographical analysis. The data source of this research is Kamus Besar Bahasa Indonesia (Third Edition). This article was written to describe the development of infixed word meaning and entries defining of infixed word. From the research, 59 -er- infixes words and fourteen meaning of -er- infixes words are found. Besides showing all of the infixes, this research also explains the five method to define entries with -er- infix which have ‘the same meaning with their bases’ in Kamus Besar Bahasa Indonesia.